Defying the IRA? Intimidation, Coercion, and Communities During the Irish Revolution - Hughes, Brian (Reappraisals in Irish History, 2017)
This book examines the grass-roots relationship between the Irish Republican Army (IRA) and the civilian population during the Irish Revolution. It is primarily concerned with the attempts of the militant revolutionaries to discourage, stifle, and punish dissent among the local populations in which they operated, and the actions or inactions by which dissent was expressed or implied. Focusing on the period of guerilla war against British rule from c. 1917 to 1922, it uncovers the acts of 'everyday' violence, threat, and harm that characterized much of the revolutionary activity of this period.